2022
DOI: 10.1136/bmjopen-2021-055326
|View full text |Cite
|
Sign up to set email alerts
|

Assessing geographical and economic inequalities in caesarean section rates between the districts of Bihar, India: a secondary analysis of the National Family Health Survey

Abstract: BackgroundIn Bihar, one of the most populous and poorest states in India, caesarean sections have increased over the last decade. However, an aggregated caesarean section rate at the state level may conceal inequities at the district level.ObjectivesThe primary aim of this study was to analyse the inequalities in the geographical and socioeconomic distribution of caesarean sections between the districts of Bihar. The secondary aim was to compare the contribution of free-for-service government-funded public fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It depicted that more than one-fifth of the institutional deliveries are C-section in most Indian provinces with maximum prevalence in southern provinces of Telangana, Kerala, and Andhra Pradesh. Another study was conducted on geographic and economic inequalities in C-section in the various districts of Bihar and reported that C-section delivery rate has increased from NFHS 4 to NFHS 5 [ 44 ]. Both these studies contend that increasing age of women, literacy of women, and economic strata are positively associated with C-section delivery in India [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It depicted that more than one-fifth of the institutional deliveries are C-section in most Indian provinces with maximum prevalence in southern provinces of Telangana, Kerala, and Andhra Pradesh. Another study was conducted on geographic and economic inequalities in C-section in the various districts of Bihar and reported that C-section delivery rate has increased from NFHS 4 to NFHS 5 [ 44 ]. Both these studies contend that increasing age of women, literacy of women, and economic strata are positively associated with C-section delivery in India [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study was conducted on geographic and economic inequalities in C-section in the various districts of Bihar and reported that C-section delivery rate has increased from NFHS 4 to NFHS 5 [ 44 ]. Both these studies contend that increasing age of women, literacy of women, and economic strata are positively associated with C-section delivery in India [ 43 , 44 ]. Critical appraisal of NFHS 5 data on maternal health indicator revealed prevalence of anaemia during pregnancy has increased from 15 to 17 provinces as compared to NFHS- 4 [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes the surgical volume indicator challenging to collect and interpret. Furthermore, surgeries, like laparoscopic surgeries for asymptomatic gallstones, cesarean sections, and so on, are performed more often as a result of advanced technologies, fewer side effects, and the fear of complications [32, 33]. This could be masking the true figure of unmet surgical need.…”
Section: Discussionmentioning
confidence: 99%